A Comparative Analysis of Truck Parking Travel Diary Data. Issue 9 (December 2018) - Boris, Caroline; Brewster, Rebecca
Critical information on the effects that truck parking shortages have on crucial stakeholders, truck drivers in particular, has historically been obtained through survey methods. However, survey methodologies rely heavily on generalizations, respondents' memory, the recency effect in memory recall, or experiences that evoked strong feelings. To investigate detailed truck parking shortage impacts using a method less reliant on historical recollections, the researchers developed and implemented a 14-day truck parking travel diary study. A total of 148 U.S. drivers participated, providing detailed data for 2, 035 days of parking activity and 4, 763 unique stops. The analysis focused on truck parking topics that have a nexus to previous survey findings that relate to drivers, state departments of transportation and enforcement activities, and other stakeholders, to facilitate the comparison of truck parking survey data with the diary data. Generally, the truck parking diary findings corroborated survey results. Almost 90% of drivers parked in an unauthorized location at least once a week – supporting survey findings that a majority of drivers find parking is difficult at least once a week. Data on unauthorized parking demonstrated that time-of-day can affect the ease of finding available parking, with peak difficulty occurring during evening hours. Drivers primarily choose parking locations for the mandated 10-h hours-of-service breaks based on practical needs – proximity to route, restroom and shower access, and expected parking availability. The research findings can provide policy, regulatory, and infrastructure guidance to both private industry and public agencies.